Continuous development of the architectural image of the city - Buinov, Alexei; Kazaryan, Armen (project baikal, 2024)
The problem of continuous development of the urban environment brings to mind the historical process of building development and the phased formation of the city image. The tasks dictated by ethical and legal restrictions when working in the historical environment are increasingly in conflict with traditional architectural creativity. This fact makes us think about the possibilities of further development of the image of the city.
Keywords: historical architectural environment; space; image of the city; person; historical development pattern